2022
DOI: 10.3390/cancers14061545
|View full text |Cite
|
Sign up to set email alerts
|

Planar Proton Minibeam Irradiation Elicits Spatially Confined DNA Damage in a Human Epidermis Model

Abstract: Purpose: High doses of ionizing radiation in radiotherapy can elicit undesirable side effects to the skin. Proton minibeam radiotherapy (pMBRT) may circumvent such limitations due to tissue-sparing effects observed at the macro scale. Here, we mapped DNA damage dynamics in a 3D tissue context at the sub-cellular level. Methods: Epidermis models were irradiated with planar proton minibeams of 66 µm, 408 µm and 920 µm widths and inter-beam-distances of 2.5 mm at an average dose of 2 Gy using the scanning-ion-mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The immunofluorescent staining of the ethanol-fixed PBMCs with γ-H2AX and 53BP1 antibodies was carried out as described by Scherthan et al [ 27 ]. The classification and evaluation of DNA damage followed the protocol described by Schumann et al [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…The immunofluorescent staining of the ethanol-fixed PBMCs with γ-H2AX and 53BP1 antibodies was carried out as described by Scherthan et al [ 27 ]. The classification and evaluation of DNA damage followed the protocol described by Schumann et al [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the results of the alkaline comet assay cannot differentiate between the formation of SSBs and DSBs, we also applied the γH2AX+53BP1 foci method to detect DSBs. This in situ stinging method can discriminate apoptotic cells [ 18 , 35 ]. The analysis of DSB-indicating foci [ 15 ] revealed that HBO exposure as well as the exposure to ambient air in the experimental chamber failed to induce an increased number of DSB foci in either cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The protons were accelerated by a 14 MV tandem accelerator to 20.5 MeV with an LET of 2.6 keV/µm. For irradiation, the SNAKE beamline was used, which is equipped to perform biological experiments with cells, tissues, and animals 26 28 . The proton beam was focused to a homogenous broad beam irradiation field with a field size of 6.5 mm × 6.5 mm.…”
Section: Methodsmentioning
confidence: 99%